"Convulsion" in a Niemann Pick Disease (NPD): A Case Report (TAJ: Journal of Teachers Association, 2010)
Niemann Pick disease is a metabolic disorder, a fatal disorder of infancy characterized by delayed developmental mile stone, failure to thrive, hepatosplenomegaly and rapidly progressive neurodegenerative changes. A 16 month female child was admitted in IBMCHR with the complaints of convulsion with ARI. She had recurrent history of ARI & convulsion. She had failure to thrive, hepatosplenomegaly delayed developmental mile stone. He was diagnosed as a case of NPD with Seizure disorder. He was treated with anticonvulsant drugs & some injectable medication as a conjurvative treatment. She was discharged with further advice & ultimately the child died. DOI: 10.3329/taj.v22i1.5038 TAJ 2009; 22(1): 139-141